A realist evaluation of the implementation of a large‐scale school eye health programme in India: a qualitative study. (16th April 2021) - Seelam, Bharani; Liu, Hueiming; Borah, Rishi Raj; Sheeladevi, Sethu; Keay, Lisa
Abstract: Purpose: This study investigates how and in what circumstances a school‐based eye health programme, the Refractive Errors Among CHildren (REACH) programme, achieved its desired outcomes: accessibility, standards of refractive care, fidelity and availability of comprehensive services, for over 2 million school children in six districts across India. Methods: We conducted a realist evaluation to identify programme aspects and their causal relationships with outcomes. Deductive and inductive thematic analysis of qualitative data included three phases: 1. theory gleaning, 2. eliciting programme theory, 3. revisiting programme theory. The Initial Programme Theories (IPTs) were developed and revised through review of the literature, programme documents and field notes. We reviewed informal and formal discussions from the participatory advisory workshops and conducted semi‐structured interviews with key stakeholders for the development and refinement of the IPTs. We based our analysis on the programme designers' perspective; used contexts, mechanisms and outcomes configuration for the analysis and presentation of the findings and reported the revised IPTs for the REACH programme. Results: We identified four major programme aspects of the REACH programme for evaluation: programme governing unit, human resource, innovation and technology and funding. Based on the intended outcomes of the programme, themes and contexts were sorted and IPTs were defined. We revised the IPTs based on the analysis of the interviews ( n = 19). The contexts and mechanisms that were reported to have potential influence on the attainment of favourable programme outcomes were identified. The revisions to the IPTs included: co‐designing a collaborative model and involving local government officials to reinforce trust, community partnerships; local well‐trained staff to encourage participation; use of the web‐based data capturing system with built‐in quality control measures and continued technical support; pre‐determined costs and targets for the outputs promoted transparency and adherence with costs. Conclusion: This process provided a comprehensive understanding of the opportunities and possibilities for a large‐scale school eye health programme in diverse local contexts in India. This illustrated the importance of embracing principles of system thinking and considering contextual factors for School Eye Health programmes in low and middle‐income countries.